Analysis of Human Activities and Deforestation Impact on Air Quality: a Paper Review - Prasetya, Ferdian Adhy; Dimyati, Muhammad; Verdyansyah, Aprizal (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This paper discusses the relationship between changes in human activities and deforestation with the condition of pollutant concentration parameters in an area using the Google Earth engine (GEE) method. By applying the Systematic Literature Review method, it is expected to provide an explanation of changes in pollutant conditions, such as concentration patterns of CO, NO2, SO2, O3, HCHO, PM2.5, and PM10 as a result of changes in human activity and deforestation. Human activity patterns may change due to certain events or rules that force humans to follow them. A clear example is the lockdown event during the Covid-19 pandemic that resulted in restrictions on human activities, especially outdoor activities. Similarly, deforestation is the process of significant reduction of forest area through tree felling, forest burning, or other land use changes that result in loss of tree cover and alter forest ecosystems. Both of these events impact the environment and air quality in the region, such as affecting air pollution concentrations. In various studies, changes in human activities and deforestation have been shown to have a significant relationship and influence on air quality concentration parameters in a region.